Comparison of the effects of sodium bicarbonate jet prophylaxis on blood pressure in normotensive individuals and patients with controlled hypertension: A controlled clinical trial - Ferreira, Camila Lopes [UNESP]; De Marco, Andrea Carvalho [UNESP]; Lazzar, Thiago Rodrigues [UNESP]; Amorim, Jose Benedito Oliveira; Santamaria, Mauro Pedrine [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (My University, 2017)
This study assessed the blood pressure (BP) of normotensive subjects and subjects with pharmacologically controlled hypertension after sodium bicarbonate jet prophylaxis. Forty subjects were divided into 2 groups: A normotensive control group (n = 20) and a hypertensive group (n = 20). Blood pressure measurements were conducted at 4 timepoints: Prior to the dental prophylaxis (T0), immediately after treatment (Ti), 15 minutes after treatment (T15), and 30 minutes after treatment (T30). The systolic BP (SBP) values for both groups were significantly increased at Ti (P < 0.05) and returned to their initial state at T15. Both groups also showed a significant increase in diastolic BP (DBP) values at Ti (P < 0.05); however, the basal conditions in hypertensive subjects were not restored until T30, whereas the values for normotensive subjects were restored at T15. The results indicated that systemic BP changed significantly after sodium bicarbonate jet prophylaxis in both study groups; while initial SBP values were restored by 15 minutes in both groups, the return to initial DBP values took longer in the hypertensive group than in the normotensive group.
Keywords: Clinical trial; Dental prophylaxis; General health; Hypertension; Sodium bicarbonate